2007
DOI: 10.1093/europace/eum234
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of inter- and intraventricular dyssynchrony in patients with heart failure according to QRS width

Abstract: A substantial proportion of patients with prolonged QRS (32.1%) did not exhibit inter- or intraventricular dyssynchrony, which may represent a limitation in identifying the ideal QRS interval for the selection of patients for CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
2
24
1
1
Order By: Relevance
“…Similar findings have emerged from another tissue Doppler study using a six basal and six middle LV segment model. [18] In the present study, however, 99% of patients with heart failure, in NYHA class III or IV, an LVEF<35% and a QRS>120 ms had dyssynchrony. With respect to patients with heart failure and a QRS<120 ms, tissue Doppler imaging studies have shown that dyssynchrony is present in 36% to 65% of patients, [5,6,19] depending on the particular method employed.…”
Section: Discussioncontrasting
confidence: 71%
“…Similar findings have emerged from another tissue Doppler study using a six basal and six middle LV segment model. [18] In the present study, however, 99% of patients with heart failure, in NYHA class III or IV, an LVEF<35% and a QRS>120 ms had dyssynchrony. With respect to patients with heart failure and a QRS<120 ms, tissue Doppler imaging studies have shown that dyssynchrony is present in 36% to 65% of patients, [5,6,19] depending on the particular method employed.…”
Section: Discussioncontrasting
confidence: 71%
“…3 One of the various reasons is that electrical dyssynchrony, as documented by QRS prolongation on a 12-lead ECG, is not synonymous with mechanical dyssynchrony; in fact, left ventricular mechanical dyssynchrony can occur in patients with normal QRS duration and vice versa. 4 In the search for better selection criteria for CRT, it has been shown that an echocardiographic assessment of left ventricular dyssynchrony is predictive for response to CRT, 5 despite large trials such as Prospect and RethinQ have failed to identify a single and accurate parameter predictor of response to therapy. 6,7 For several years, tissue Doppler imaging (TDI) was the standard and predominant echocardiographic technique for quantification of mechanical dyssynchrony.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Fahmy Elnoamany et al [2] showed that patients with acute MI may have LV systolic asynchrony even in the absence of QRS widening or bundle branch block. In contrast, according to another report by Emkanjoo et al [3] , about 32.1% of patients with prolonged QRS do not exhibit interor intraventricular asynchrony. So we think it is not a very rigorous approach to assume that post-MI patients with IVCD have myocardial asynchrony and those without IVCD represent the normal contrast.…”
mentioning
confidence: 77%